Displacements in Mechanical Systems Due to Random Inputs in a Mine Hoist Installation - WOLNY, Stanisław (Engineering Transactions, 2017)
Conveyances, cages and skips are typical components of hoisting installations in mines. The Authors emphasises the fact that already at the stage of design utmost care must be taken to reduce the skip’s own mass, at the same time improving its reliability through controlling the deformations of its structural elements. That requires, however, a thorough analysis of the state of stress in the conveyance’s load-bearing elements due to real loads acting both during the normal duty cycles and under the emergency conditions. Real loads acting upon the load bearing elements of the conveyance were determined following the analysis of displacements of selected points of the conveyance’s structure. For the purpose of calculation procedure, the conveyance is substituted by a triple mass model whose dynamic motion equations are based on an assumption that horizontal displacements of the skip mass are induced by random irregularities and misalignments of guiding strings. These equations are solved analytically, yielding the spectral densities of displacements of selected masses. Thus derived formulas and their graphical representations allow for selecting the system’s parameters such that the displacements of the selected model points should not exceed the admissible levels set forth in relevant mining regulations.